Homesickness, Depression and Happiness in University Students of Hamadan, Iran - Babak Moeini; Hamid Abasi; Maryam Afshari; Morteza Haji Hosseini; Ali Ghaleiha (Shahrekord University of Medical Sciences, 2018)
Background and aims: Students are exposed to multiple various mental disorders. One of the most important difficulties the students encounter are homesickness and depression the occurrence of which cause less happiness in the students. This study was conducted to investigate the relationship among 3 factors of homesickness, depression, and happiness in dormitory students of Hamedan University of Medical Sciences. Methods: A cross-sectional study was carried out on 387 dormitory students of Hamedan University of Medical Sciences from January to April 2016. The participants of the study were selected through stratified random sampling technique with proportional allocation. Data were collected through self-reporting and four questionnaires including demographic data questionnaire, homesickness Benfleet questionnaire, University Students Depression Inventory (USDI), and Oxford happiness questionnaire. A quantitative analysis of the inquiry was performed using SPSS software, version 23. Results: The results showed that depression had an indirect relationship (-0.6) with happiness. That is, by increasing the depression scores happiness will decrease. In addition, depression had a significantly direct relationship (0.3) with homesickness. It implies that an increase in homesickness score leads to an increase in depression score. Moreover, homesickness had a significantly indirect relationship (-0.2) with happiness. Namely, an increase in homesickness, results in a decrease in happiness. Conclusion: In view of the results obtained and given the importance of mental health of the students in dormitories, it seems that the reasons related to homesickness and depression should be recognized and included in intervention and prevention programs. Besides, appropriate interventions must be designed and implemented in this regard.